Gaya Public Speaking Mc Dangdut Velozta Musik Dalam Memeriahkan Acara - A’id Dzatia; Primi Rohimi (Program Studi Komunikasi dan Penyiaran Islam, STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
Indonesian people have a great interest in dangdut music which has become the musical identity of the archipelago, causing the profession of Master of Ceremony (MC) to be much needed nowadays. The MC profession is currently considered a glamorous job because you can meet important people. The aim of this research is to analyze the techniques and public speaking styles of the dangdut MC music group Velozta. The research methods used are qualitative research methods in data processing, and interview methods, observation as data collection techniques. The research results show that when implementing a dangdut MC you must master several techniques such as preparation, vocal training, and guiding the event from start to finish. Analysis of public speaking style shows that the dangdut MC Velozta Music has good vocals and the ability to speak calmly and not in a hurry. Dangdut MC Velozta music is able to create an interactive atmosphere and also include humor when talking to the audience or singers. What differentiates a dangdut MC from MCs at other events is that a dangdut MC is very interactive and very friendly with the audience, for example offering song requests at every singing session. This makes the audience feel appreciated and not bored. The public speaking style of a dangdut MC will determine the success and excitement of the dangdut event